Production of alkaline protease from Cellulosimicrobium cellulans - Ferracini-Santos,Luciana (2009)
Cellulosimicrobium cellulans is one of the microorganisms that produces a wide variety of yeast cell wall-degrading enzymes, β-1,3-glucanase, protease and chitinase. Dried cells of Saccharomyces cerevisiae were used as carbon and nitrogen source for cell growth and protease production. The medium components KH2PO4, KOH and dried yeast cells showed a significant effect (p<0.05) on the factorial fractional design. A second design was prepared using two factors: pH and percentage of dried yeast cells. The results showed that the culture medium for the maximum production of protease was 0.2 g/l of MgSO4.7H2O, 2.0 g/l of (NH4)2SO4 and 8% of dried yeast cells in 0.15M phosphate buffer at pH 8.0. The maximum alkaline protease production was 7.0 ± 0.27 U/ml over the center point. Crude protease showed best activity at 50°C and pH 7.0-8.0, and was stable at 50°C.